Nabalus muliensis (Asteraceae, Cichorieae), a new species from China - Chen, You-Sheng; Xu, Lian-Sheng; Ke, Rui (Phytotaxa, 2019)
Nabalus muliensis (Asteraceae, Cichorieae), a new species from southwestern Sichuan, China, is described and illustrated. It is the third species of Nabalus occurring in China. The new species is similar to Nabalus tatarinowii in its paniculiform inflorescence, nodding capitula, 3–5 florets, cylindric involucre, achene with unequal ribs and pale brown pappus, but differs by its yellow florets (vs. purple, white or pink), leaf blade lyrate-pinnatilobate (vs. divided with 1–3 pairs of lobes), and achenes with a 2–3 mm long beak (vs. apex truncate). The new species is considered Endangered (EN) according to the IUCN Red List Categories and Criteria.